Miniatur Sistem Pembangkit Listrik Tenaga Air Piko Hidro Sebagai Media Pembelajaran Pada Politeknik Bosowa - Irvawansyah, Irvawansyah; Nur Fitri, Sulistianingsih; Ibnu Munsyir, Andi Muhammad (Department of Electrical Engineering, University of Patria Artha, 2020)
This study aims to make a miniature Pico Hydro-Hydro Power Plant (PH-HPP) system with load variations. The research method used in this research consists of the stages (1) identification of the problem, (2) design, (3) development and (4) application. Based on the results of observations at the development stage, the number of revolutions using one nozzle was greater than 29%, namely 1080 rpm for one nozzle and 758 rpm for 2 nozzles. The measured output voltage when using a 3 watt load is 142 VAC and the measured voltage when using a 100 watt load is 106 VAC. The measured output voltage on the control panel is inversely proportional to the load given, and this is because the higher the wattage load on the lamp, the heavier the generator rotates so that the output voltage on the generator is getting smaller.